Chemotaxis Assay for Marsupenaeus japonicas Hemocytes and Application for the Development of an Oral Immunostimulant Against White Spot Syndrome Virus - Imai, Takashi; Takahashi, Yukinori (Frontiers in Cell and Developmental Biology, 2020)
The chemotactic activity of vertebrate leukocytes is an important bio-defense mechanism. However, chemotaxis of invertebrate immune cells, particularly those of shrimp species, is incompletely understood and critically understudied. In this study, we aimed to optimize the conditions for a Boyden chamber chemotaxis assay using hemocytes from shrimp, Marsupenaeus japonicas and the optimal conditions were: 5 μm-pore-size Polyvinylpyrrolidone membrane; culture buffer at pH 7.0; and chemotactic factor N-formyl-methionyl-leucyl-phenylalanine (fMLP) 10-8 mol/L; 4 hours incubation time. We then applied the chemotaxis assay to develop an oral immunostimulant against white spot syndrome virus (WSSV), which results in high mortality rates in several shrimp species worldwide. We focused on the kelp Laminaria japonica, as this species contains immunostimulative molecules such as β-glucan. We prepared Heat Extracts (HE) and Crude Laminarans (CL) from kelp using hot water and hydrochloric acid extraction methods, respectively. Kelp extracts were orally administered for 7 days, and hemocyte chemotaxis towards fMLP was compared. No difference was detected between control and kelp extracts on day 3, but HE stimulated chemotaxis 2-fold and CL stimulated chemotaxis 3-fold relative to control on day 7 after initiating administration. Kelp extract administration protected against WSSV exposure. Finally, we identified that Kelp extracts stimulated hemocyte superoxide production on day 3 and day 7, and increased hemocyte phagocytosis and phenol-oxidase activity on day 7 after administration. We concluded that the chemotaxis assay is informative in assessment of shrimp hemocyte immunological activity, and is applicable to the development of immunostimulants against shrimp infectious diseases.